THE EFFECTIVENESS OF USING BUSUU APPLICATION ON STUDENTS’ LISTENING SKILL AT EIGHT GRADE STUDENTS IN SMP NEGERI 37 MEDAN - Putri Sinta Diana Simamora; Rina Octavia Simarmata; Sahat Taruli Siahaan (Jurnal Scientia, 2023)
This research aimed to determine the effectiveness of Busuu application on the listening skill of eight grade students at SMP Negeri 37 Medan. Research design in this study was an experimental quantitative research design, in one class and this research was conducted in SMP Negeri 37 Medan. The sample in this research was 29 students from class VIII H. Data obtained by doing listening test. After conducting the research and analyzed data, the writer concluded that the Busuu application can be effectively used as a medium for students’ listening skill, this was evidenced by the students' average scores in the pre-test and post-test. The results showed that the mean score increased from 68.10 in the pre-test to 81.20 in the post-test. It was discovered that the mean score for the post-test is greater higher than the mean score for the pre-test. α = 0.05 is the level of significance determined by the t-observed > t-table (20 > 1.701). This indicates that the alternative hypothesis (H_a) is accepted and the null hypothesis (H_o) is rejected. This means that the Busuu application can be effectively used as a medium for students’ listening skill of eight grade students at SMP Negeri 37 Medan.